Clock and clock-controlled genes are differently expressed in the retina, lamina and in selected cells of the visual system of Drosophila melanogaster - Damulewicz, Milena; Loboda, Agnieszka; Bukowska-Strakova, Karolina; Jozkowicz, Alicja; Dulak, Jozef; Pyza, Elzbieta (Frontiers in Cellular Neuroscience, 2015)
The retina and the first optic neuropil (lamina) of Drosophila show circadian rhythms in various processes. To learn about the regulation of circadian rhythms in the retina and lamina and in two cell types, glial and the lamina L2 interneurons, we examined expression of the following clock genes; per, tim, clk, and cry and clock-controlled genes; Atp, nrv2, brp, Pdfr. We found that the expression of gene studied is specific for the retina and lamina. The rhythms of per and tim expression in the retina and glial cells are similar to that observed in the whole head and in clock neurons, while they differ in the lamina and L2 cells. In both the retina and lamina, CRY seems to be a repressor of clk expression. In L2 interneurons per expression is not cyclic indicating the other function of PER in those cells than in the circadian molecular clock. In contrast to per and tim, the pattern of clk and cry expression is similar in both the retina and lamina. The retina holds the autonomous oscillators but the expression of cry and clock-controlled genes, Atp and nrv2, is also regulated by inputs from the pacemaker transmitted by PDF and ITP neuropeptides.